Detection of Semantically Equivalent Fragments for Business Process Model Change Management - Gerth, Christian; Luckey, Markus; Küster, Jochen; Engels, Gregor
Modern business process modeling environments support distributed development by means of model version control, i.e., comparison and merging of two different model versions. This is a challenging task since most modeling languages support an almost arbitrary creation of process models. Thus, in multi-developer environments, process models or parts of them are often syntactically very different but semantically equivalent. Hence, the comparison of business process models must be performed on a semantic level rather then on a syntactic level. For the domain of business process modeling, this problem is yet unsolved. This paper describes an approach that allows the semantic comparison of different business process models using a normal form. For that purpose, the process models are fully automatically translated into process model terms and normalized using a term rewriting system. The resulting normal forms can be efficiently compared. Our approach enables the semantic comparison of business process models ignoring syntactic redundancies.

Full Semantics Preservation in Model Transformation - A Comparison of Proof Techniques - Hülsbusch, Mathias; König, Barbara; Rensink, Arend; Semenyak, Maria; Soltenborn, Christian; Wehrheim, Heike

Applying heuristic methods for job scheduling in storage markets - Finkbeiner, Josef; Bodenstein, Christian; Schryen, Guido; Neumann, Dirk (18th European Conference on Information Systems (ECIS 2010))
In double-sided markets for computing resources an optimal allocation schedule among job offers and requests subject to relevant capacity constraints can be determined. With increasing storage demands and emerging storage services the question how to schedule storage jobs becomes more and more interesting. Since such scheduling problems are often in the class NP-complete an exact computation is not feasible in practice. On the other hand an approximation to the optimal solution can easily be found by means of using heuristics. The problem with this attempt is that the suggested solution may not be exactly optimal and is thus less satisfying. Considering the two above mentioned solution approaches one can clearly find a trade-off between the optimality of the solution and the efficiency to get to a solution at all. This work proposes to apply and combine heuristics in optimization to gain from both of their benefits while reducing the problematic aspects. Following this method it is assumed to get closer to the optimal solution in a shorter time compared to a full optimization.
Keywords: Decision Support System; Algorithms; Optimization; Market Engineering

From "Take-it-or-leave-it" offers to "Take-it-or-be-left-out" Ultimatum - A trade mechanism for Online Services - Bodenstein, Christian; Schryen, Guido; Neumann, Dirk (18th European Conference on Information Systems (ECIS 2010))
In a world, where more and more businesses seem to trade in an online market, the supply of online services to supply the ever-growing demand could quickly reach its capacity limits. Online service providers may find themselves maxed out at peak operation levels during high-traffic timeslots but too little demand during low-traffic timeslots, although the latter is becoming less frequent. At this point not only deciding which user is allocated what level of service becomes essential, but also the magnitude of the service provided, can be controlled by pricing. Pricing is an important factor when efficient and acceptable allocation of resources between individuals must be reached. Without prices, transferring or sharing goods would be impossible. In sharing information, pricing a product however is not as simple as relatively pricing an apple or a pear. Often the costs, and hence the prices are simply unknown. Backed by this scenario, the online services market could be combined with the market design mechanism of diamonds. For this we propose an ultimatum pricing strategy which effectively allows for valuations to be accounted for, but no longer a necessity when pricing in grid, cloud or other online computing environments.
Keywords: Posted Price; Ultimatum Game; Energy Efficiency; Mechanism Design

Geschäftsmodelle in virtuellen Spielwelten

Erfolgsfaktoren von Testprozessbewertungsmodellen - Brüseke, Frank; Sancar, Yavuz; Yigitbas, Enes (Proceedings of the Conference on Software & Systems Engineering Essentials 2010 (SEE 2010), Köln (Germany))

Editorial: Aufschwung mitgestalten - Kabst, Rüdiger

HR Business Partner gesucht - Kabst, Rüdiger; Kötter, P M; Meifert, M; Wehner, M C

Editorial: Verdrängte Herausforderung Demographie - Kabst, Rüdiger

Was High-Performer besser machen: Was unterscheidet erfolgreiche von weniger erfolgreichen Unternehmen beim Employer Branding? - Kabst, Rüdiger; Baum, M; Fortange, A